Analisis Dampak Pembangunan Pariwisata Pasar Kamu Pada Aspek Ekonomi Dan Sosial Budaya Masyarakat - Padilla Hawanda; Ila Nasution; Nurhayati Harahap (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Denai Lama Village, located in Pantai Labu District, Deli Serdang Regency, has significant tourism potential, which can be a source of income and improve the welfare of the local community. The focus of this research is on analyzing the economic and socio-cultural aspects of tourism development. The method used is a qualitative method with the aim of describing and analyzing the impact of tourism development on the community of your market tourism village. Data is collected from various sources such as books, journals and previous research to support research. The research results show that tourism development has a positive impact on additional income, job creation, cultural exchange and preservation of local traditions. This shows the potential for sustainable tourism development in the Old Denai village.